Populism and Institutional Capture - Nicholas Chesterley; Paolo Roberti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
This paper considers electoral behavior and institutional capture when voters choose between a populist and non-populist politician. Populist politicians provide voters with a utility boom followed by a subsequent bust, as in Dornbusch and Edwards (The Macroeconomics of Populism in Latin America, University of Chicago Press, 1991). Non-populists provide a constant level of utility. Once in power, however, politicians of both types are able to seize control of institutions to ensure their re-election. We show that in equilibrium, populist politicians may capture institutions to avoid being replaced during the bust: non-populists do not. Voters rationally elect a populist if voters discount the future sufficiently or if it is too costly for the populist to seize control of institutions. Unfortunately, both types of politician may prefer weakened institutions, either to allow their capture or to discourage the election of the populist.
Keywords: D72; D73; D74; 330